CINNAMON EXTRACT (cinnamomum cassia) AGAINST DIABETES MELLITUS - Hartawan (Journal of Holistic and Traditional Medicine, 2021)
Diabetes mellitus, or better known to the public with the disease diabetes is a collection of metabolic disorders that produce the same symptom, namely hyperglycemia. Diabetes patients usually use synthetic drugs to control their blood glucose, however, long-term use often causes unwanted side effects, some patients switch to or supplement their therapy with alternative treatments, one of which is herbal medicine. There are various herbal remedies to prevent or treat diabetes, depending on the type of plant used and how to process and consume them, including cinnamon. Use of cinnamon as a therapy for headaches, loss appetite, dyspepsia, flu, inflammation, wound healing, nausea, and diarrhea are quite widespread in society.